DIFFERENT DOSAGES OF INERT DUST AND TEMPERATURES IN STORAGE CORN FOR CONTROL OF MAIZE WEEVIL - CANEPPELE, Maria Aparecida Braga; ANDRADE, Patrícia de Jesus; SANTAELLA, Alexandre Garcia (Scientia Agraria, 2010)
In Brazil, Sitophilus zeamais Mots. and S. oryzae L. (Coleoptera: Curculionidae) are among the most important insects for the corn grains and stored rice, respectively, causing quantitative and qualitative losses. The diatomaceous earth has been studied by several researchers, for the protection of stored grains. The research aimed to evaluate the effectiveness of the inert dust in different dosages and temperatures for the S. zeamais’ control in grains of stored corn. Samples of 400 g of corn were packed in glass flasks with lid covered by nylon fabric and submitted to the following treatments: Inert dust in the dosages of 0, 125, 500 and 750 g t-1 upon temperatures of 25, 30 and 35 °C, in five replicates. Each flask received 30 adult insects of S. zeamais for the mortality evaluations with three, seven, 14, 21 and 28 days. There were not statistical difference for the dosages of 500 and 750 g.t-1, in the three studied temperatures. On temperatures of 25 and 30° C the dosages of 500 and 750 g t-1 became efficient from the seventh evaluation day. In the temperature of 35 °C the three dosages, on third evaluation day, obtained almost 100% of mortality. The diatomaceous earth demonstrated as effective treatment in the control of S. zeamais. The 500 g t-1 dosage can be recommended for the control of S. zeamais on stored corn in temperatures above 25 °C.